The Yazidi Survivors Between the Tragedy of the Genocide and the Reality of the Camps (A field study of the reality of the survivors of ISIS captivity) - حمزة رنا جاسم محمد (Tasnim International Journal for Human, Social and Legal Sciences, 2023)
The camps are a cumulative assembly that does not constitute a sense of belonging and does not constitute a coherent social body. Therefore، the camps were not prepared to meet the needs، and are not suitable for practicing work except in the most limited limits، almost creating a feeling for those who live in them that they are neglected، and that life in the camps reminds the survivors Every day، with what they have lost، they find themselves in a vicious circle. It is clear that the issue of Yazidi women has become a general humanitarian and social issue on the one hand، and a special issue related to women and the forms of kidnapping، rape and violence they have been subjected to. This study seeks to examine the situation of Yazidi girls and women after their return from kidnapping، and about the reality of the services provided to them by some international and local organizations. Based on the importance of documenting these services provided to women and girls in displacement camps، the study focuses on the service frameworks provided to them، as it is an important step in knowing the size of the gap in the protection services provided to them، and the study contributes to identifying the priorities that must be taken into account when developing plans future to achieve better conditions for Yazidi women survivors of violence. The study shows that women are suffering from multiple forms of violations committed against them، as women have suffered a lot from the effects of the control of (ISIS) gangs from kidnapping، rape and forced marriage، as well as forcing them to convert to the Islamic religion، Women still suffer from an unknown fate، as girls and women today have become widows or orphans in situations devoid of protection and support mechanisms. Most of the survivors، whether residing in the camps or residing outside the camps، lack health services، including psychological and social support. This study aims to identify the social and economic conditions that Yazidi women live in the camps، with the identification of the most important services provided to Yazidi women and their effectiveness in covering their needs. Given the importance of this study، we will rely on the case study method، because it reveals to us closely the real and actual conditions of the Yazidi women’s conditions after their return inside the camps.